Strategic Risk Management and Organizational Resilience in Rwanda: A Case of Military Medical Insurance - Uwitonze, Jean; Njenga, Gitahi (International Journal of Strategic Management, 2024)
Purpose: The general objective of the research was to assess the effect of strategic risk management on Organizational Resilience in Rwanda. Specifically, the study determined the effect of strategic risk identification on resilience of Military Medical Insurance, find out the effect of strategic risk assessment on resilience of Military Medical Insurance and analyzed the effect of strategic risk mitigation on resilience of Military Medical Insurance. Methodology: The study employed descriptive and correctional research design. This research aims to gather data from 173 individuals who work for various divisions within Rwanda's Military Medical Insurance. Using Slovin's formula, the researcher determined the number of participants needed for the sample. 121 participants in their sample, out of a total population of 173. The researcher used questionnaire and interview guide to collect primary data. The researcher used SPSS (Statistical Package for Social Scientists, Version 25) for data analysis. Findings: The model reveals a multiple correlation coefficient (R) of 0.883, indicating a strong positive relationship between these predictors and organizational resilience at Military Medical Insurance. The R Square value of 0.780 suggests that approximately 78.0% of the variance in organizational resilience can be explained collectively by these independent variables, showcasing a significant level of explanatory power. Furthermore, the Adjusted R Square of 0.774 demonstrates that even after adjusting for the number of predictors, 77.4% of the variance in organizational resilience is accounted for by the model, reinforcing its robustness. Unique Contribution to Theory, Practice and Policy: The study recommends that Military Medical Insurance adopt a comprehensive risk management framework that emphasizes continuous risk identification, assessment, and mitigation. Specific recommendations include implementing regular training sessions on risk management for staff, integrating advanced analytical tools to assess potential risks accurately, and fostering a culture of open communication regarding risk factors.